Freedom of navigation and combating illegal activities on the high seas for safety of maritime navigation - Bitam, Adel (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
This study discusses the freedom of navigation on the high seas. Many problems exist that jeopardise the safety of maritime navigation in this zone. The concept of freedom of navigation on the high seas emerged under the rules of international customary law and was further organised under conventional law. Therefore, no State can claim any part of the high seas as its territorial sea. This principle was adopted in the 1958 Geneva Convention on the High Seas and also in the 1982 Convention on the Law of the Sea (UNCLOS). The right of navigation essentially stipulates that every State whether coastal or land-locked has the right to sail. Freedom of navigation has always been threatened due to numerous aggressions, attacks and killings as a result of piracy and slave trading to name but two reasons, which in turn threatens the security of the States where they interfere. The danger has increased in the beginning of the twentieth century with the development of international trade and maritime transportation. Many crimes have emerged, example of which include maritime terrorism, drug trafficking, smuggling of migrants and the use of weapons of mass destruction against many vessels including commercial, military and touristic vessels. In contrast, exclusive jurisdiction of the flag State is not sufficient to combat these crimes. In addition, it must be through a cooperation of international community that these crimes can be minimised in order to guarantee the safety of maritime navigation on the high seas. This can only be brought about through the many efforts of combating and punishment. The high seas are considered a sensitive area and therefore the UNCLOS has reserved them only for peaceful purposes.